2020
DOI: 10.1007/s10719-020-09935-x
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids and plasma membrane hydrolases in human primary bronchial cells during differentiation and their altered patterns in cystic fibrosis

Abstract: Human primary bronchial epithelial cells differentiated in vitro represent a valuable tool to study lung diseases such as cystic fibrosis (CF), an inherited disorder caused by mutations in the gene coding for the Cystic Fibrosis Transmembrane Conductance Regulator. In CF, sphingolipids, a ubiquitous class of bioactive lipids mainly associated with the outer layer of the plasma membrane, seem to play a crucial role in the establishment of the severe lung complications. Nevertheless, no information on the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Most likely, the changes in ceramide and PUFA metabolism are caused, at least in part, by translational and posttranslational events such as trafficking and enzyme compartmentalization which, could alter metabolic flux and steady-state levels of ceramides and PUFAs. Using a pulse labeling technique to quantitate sphingolipids, Loberto et al (2020) recently reported enhanced ceramide and ganglioside levels specifically in the apical membrane of CF compared to non-CF in primary airway epithelial cells, differentiated 7 days at the ALI, associated with a change in relative localization of sphingolipid metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, the changes in ceramide and PUFA metabolism are caused, at least in part, by translational and posttranslational events such as trafficking and enzyme compartmentalization which, could alter metabolic flux and steady-state levels of ceramides and PUFAs. Using a pulse labeling technique to quantitate sphingolipids, Loberto et al (2020) recently reported enhanced ceramide and ganglioside levels specifically in the apical membrane of CF compared to non-CF in primary airway epithelial cells, differentiated 7 days at the ALI, associated with a change in relative localization of sphingolipid metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sphingosine, studies from several laboratories have demonstrated that ceramide levels are higher in CF epithelial cells than in normal cells (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The imbalance between ceramide and sphingosine in the respiratory tract was shown to be mediated by a down-regulation of the acid ceramidase protein expression correlating with a marked reduction of the activity of the acid ceramidase in tracheal and bronchial epithelial cells of mice and humans (9,19).…”
Section: Staphylococcus Epidermidismentioning
confidence: 99%
“…Our data showing that the mRNA and protein levels for IRF8 are markedly increased in fully differentiated human tracheal epithelial cells suggests that CFTR/Cftr regulates IRF8 transcription. On the other hand it has been previously shown impaired in CF cells and, consistent with our data employing a proteasome inhibitor, it is unlikely that the expression of IRF8 is increased by a defect in the proteasome.It might be possible that deficiency of CFTR/Cftr results in an alkalization of lysosomes(6,30) and thereby in addition, it was shown that ceramide synthesis is upregulated in CF cells and might also cause or contribute, respectively, to an initial increase of ceramide(15,17,31). Thisinitial rise of ceramide might trigger, via unknown mechanisms, the upregulation of IRF8, which then results in a physical down-regulation of acid ceramidase expression and thereby in further accumulation of ceramide and depletion of sphingosine, finally resulting in a vicious cycle in CF cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have recently reported that the lipid composition of CF airway epithelial cells is significantly altered with an increase of ceramide and a decrease of sphingosine in the luminal membrane of tracheal and bronchial epithelial cells (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%